Assessment of Activity Daily Living of Children with Autism Spectrum Disorder - Saputra, Siti Dedah Holidah; Aprilia, Imas Diana; Susetyo, Budi (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Daily living activities are very important for children with autism spectrum disorders to master so that they are independent, but there are still children with autism who have not fully mastered these daily living activity skills. This study aims to determine the abilities and disabilities of children with autism spectrum disorders in daily living activities. The focus of research in this study was a grade 4 autistic student at SDLB Al-Ishlah Purwadadi, Subang Regency. The research method used is a descriptive method in the form of a case study with a qualitative approach. The results of this research are that the abilities of autistic students in activity daily living have not been fully mastered by children, around 61% of activity daily living are still assisted by parents in doing it.